Phlolosides A–F, iridoids from Phlomis likiangensis with a carbonate ester substituent. Issue 32 (9th August 2017) - Li, Xiao-Hui; Li, Xu-Hong; Yao, Qi; Lu, Li-He; Li, Yun-Biao; Wu, De-Song; Fu, De-Huan; Mei, Shuang-Xi; Cui, Tao; Wang, Jing-Kun; Zhu, Zhao-Yun
Graphical abstract: Highlights: This is the first phytochemical exploration on the Phlomis likiangensis. Six new iridoid glycosides (1 –6 ), namely phlolosides A–F, were isolated and structural elucidated. This is the first report of iridoid glycosides with a carbonate ester group. The antibacterial and cytotoxic activities of these new iridoid glycosides are reported. The absolute configuration of1 was determined by single crystal X-ray diffraction analysis. Abstract: Chemical study on the aerial parts of Phlomis likiangensis unearthed six new iridoid glycosides, phlolosides A–F (1 –6 ), together with six known analogues (7 –12 ). In the light of a combination of spectroscopic data, acid hydrolysis and single crystal X-ray diffraction analysis, the structures of1 –6 were determined. This is the first discovery of iridoid glycosides assembling a carbonate ester substituent group. All isolated compounds were assayed for cytotoxic and antibacterial activities, but were either inactive or very weakly active.